A conceptual framework for community interventions in successful aging - Caron, Catherine M (University of Ottawa (Canada), 2005)
As the number and percentage of elderly Canadians increase, it becomes imperative to understand successful aging in order to keep this growing segment of our population healthy and productive. Conceptual models of successful aging have been proposed in a number of disciplines (biology, psychology, sociology, epidemiology), but these have yet to be integrated. There is not even agreement on how to define successful aging, or on whether it is a state of being or an adaptive process. To date, there have been relatively few interventions to promote successful aging, and the lack of a theoretical approach makes it more difficult to design them and to assess the results of any interventions that have been attempted. In this thesis, I build upon the insights from existing literatures, and I propose a conceptual model for successful aging. I then discuss the application of this model to guide community interventions for Successful Aging Ottawa.
Keywords: Gerontology.; Health Sciences, Public Health.